Trait Repetitive Negative Thinking: A Brief Transdiagnostic Assessment - McEvoy, Peter; Tribodeau, M.; Asmundson, G. (Textrum Ltd, 2014)
Repetitive negative thinking (RNT) is an established transdiagnostic process associated with multiple emotional disorders. Brief transdiagnostic measures of RNT uncontaminated with diagnosis-specific symptoms, terminology, and instructions are required for (a) research investigating the process of RNT and (b) clinical practice to guide case formulations, treatment plans, and to assess change. The aim of this study was to examine the psychometric properties of a 10-item trait version of the Repetitive Thinking Questionnaire (RTQ-10) in undergraduate (N = 386) and clinical (N = 400) samples. The undergraduate sample completed the RTQ-10, and the clinical sample completed the RTQ-10 as well as measures of worry, rumination, anxiety- and depression-related cognitions, and positive and negative affect. Results demonstrated that the RTQ-10 has a unitary structure, high internal reliability, distinguishes between clinical and non-clinical cases, assesses RNT similarly in men and in women, and accurately assesses RNT along its full continuum. RTQ-10 scores were positively associated with worry and rumination, anxiety and depression symptoms and cognitions, and with the higher order vulnerability factor of negative affect, adding to its transdiagnostic credentials. The RTQ-10 was negatively but weakly associated with positive affect, providing some divergent validity. The RTQ-10 appears to be a brief and clinically useful transdiagnostic measure of RNT